Prescription drug shortages: Impact on neonatal intensive care - Ziesenitz, Victoria C. (Neonatology, 2019)
Background: Prescription drug shortages have increased significantly during the past two decades and also impact drugs used in critical care and pediatrics. Objectives: To analyze drug shortages affecting medications used in neonatal intensive care units (NICUs). Methods: Drug shortage data for the top 100 NICU drugs were retrieved from the University of Utah Drug Information Service from 2001 to 2016. Data were analyzed focusing on drug class, formulation, reason for shortage, and shortage duration. Results: Seventy-four of the top 100 NICU drugs were impacted by 227 shortages (10.3% of total shortages). Twenty-eight (12.3%) shortages were unresolved as of December 2016. Resolved shortages had a median duration of 8.8 months (interquartile range 3.6-21.3), and generic drugs were involved in 175 (87.9%). An alternative agent was available for 171 (85.8%) drugs but 120 (70.2%) of alternatives were also affected by shortages. Parenteral drugs were involved in 172 (86.4%) shortages, with longer durations than nonparenteral drugs (9.9 vs. 6.4 months, p = 0.022). The most common shortage reason was manufacturing problems (32.2%). Conclusions: Drug shortages affected many agents used in NICUs, which can have quality and safety implications for patient care, especially in extremely low birth weight infants. Neonatologists must be aware of current shortages and implement mitigation strategies to optimize patient care.
Published online: November 01, 2018
Gesehen am 24.05.2019